2010
DOI: 10.1038/emboj.2010.122
|View full text |Cite
|
Sign up to set email alerts
|

Dis3-like 1: a novel exoribonuclease associated with the human exosome

Abstract: The exosome is an exoribonuclease complex involved in the degradation and maturation of a wide variety of RNAs. The nine‐subunit core of the eukaryotic exosome is catalytically inactive and may have an architectural function and mediate substrate binding. In Saccharomyces cerevisiae, the associated Dis3 and Rrp6 provide the exoribonucleolytic activity. The human exosome‐associated Rrp6 counterpart contributes to its activity, whereas the human Dis3 protein is not detectably associated with the exosome. Here, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
149
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(157 citation statements)
references
References 39 publications
7
149
0
1
Order By: Relevance
“…The catalytic activity is provided by a 10th essential subunit, Rrp44p (2,5,6). This protein is similar to RNase II in that it contains three putative RNA binding domains that flank an RNB domain (3,(7)(8)(9)(10).…”
Section: Dis3 | Saccharomyces Cerevisiaementioning
confidence: 99%
“…The catalytic activity is provided by a 10th essential subunit, Rrp44p (2,5,6). This protein is similar to RNase II in that it contains three putative RNA binding domains that flank an RNB domain (3,(7)(8)(9)(10).…”
Section: Dis3 | Saccharomyces Cerevisiaementioning
confidence: 99%
“…[15][16] Interestingly, the single human Rrp6 protein is found not only in the nucleus (with nucleolar enrichment typical of exosome ring proteins) but also in the cytoplasm, unlike its yeast counterpart. [17][18] In plants on the other hand, while only one protein of the Dis3 family is encoded in currently known plant genomes, three genes of the RRP6 family are present in Arabidopsis, rice and poplar, encoding the proteins AtRRP6L1, AtRRP6L2 and AtRRP6L3 in Arabidopsis.…”
Section: Exosome Compositionmentioning
confidence: 99%
“…Surprisingly, however, the human RRP6 factor (hRRP6, also designated PM/Scl-100) was reported to be present in both the nucleus and cytoplasm (Brouwer et al, 2001;van Dijk et al, 2007), whereas DIS3 was not found in exosome preparations (Chen et al, 2001). Tomecki et al (2010) and Staals et al (2010) now report that the genome from human beings and some other higher eukaryotes encodes three DIS3 paralogs: hDIS3, DIS3-like 1 (hDIS3L1) and DIS3-like 2 (hDIS3L2). Functional analysis indicates that these proteins have different functions as only hDIS3 complements a yeast DIS3 deletion.…”
mentioning
confidence: 99%
“…Recent analysis of higher eukaryotic exosomes reveals some differences challenging this idea. In this issue of The EMBO Journal, Tomecki et al (2010) and Staals et al (2010) provide new insights into the composition and function of the human exosome, with implications for our understanding on the organization, function and localization of this complex in these cells.The exosome is responsible for many RNA processing and degradation reactions in the nucleus and cytoplasm (Lykke-Andersen et al, 2009). Yeast exosome is composed of a nine subunit ring structure to which Dis3 binds to form the exosome core.…”
mentioning
confidence: 99%
See 1 more Smart Citation